Examining the accumulated oxygen deficit method in breaststroke swimming - Reis, Victor M (2020)
Submitted by Daniel Marinho (dmarinho@ubi.pt) on 2020-02-12T20:44:05Z No. of bitstreams: 1 98 - reis2010.pdf: 328316 bytes, checksum: 944616135d80ea3f1ae27879d84e0300 (MD5)